Like Any Other Trap: The Circuitous Path of Student Loan Repayment. (May 2022) - Furquim, Fernando; Deane, KC; McCall, Brian P.; DesJardins, Stephen L.
This paper studies the patterns of individuals' student loan repayment for up to 12 years, tracking borrowers through the formative ages of the early 20s to the late 30s. Using social sequence and cluster analysis to understand these longitudinal repayment histories, we identify five archetypes of loan repayment that describe borrowers' experiences: persistent defaulters, perpetual payers, rapid full payers, late full payers, and consolidators. We find significant stratification by race/ethnicity, social class, and institutional sector into repayment clusters, with minoritized borrowers and those attending for-profit institutions more likely to experience adverse borrowing outcomes and to experience them for longer.